The level of linguistic literacy among students of the arabic language department - AL. Zuwaini, Ibtisam Sahib Mussa; Hamid, Raida Hussein (Opción, 2019)
This study aimed to identify the level of linguistic literacy among the students of the college of basic education and its relation to the gender variable via the descriptive approach. The results showed the low level of linguistic literacy among students of the College of Basic Education and the existence of statistically significant difference in the gender variable for females. In conclusion, the rate of the general average of the gender variable in the Arabic Language Department materials indicated the superiority of females on males and this was confirmed by many studies, which concluded that females exceed males in reading.